The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1164/rccm.201611-2268oc
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Heart–Lung Interactions in Ventilator-induced Lung Injury

Abstract: In a classic model of ventilator-induced lung injury, high peak pressure (and zero positive end-expiratory pressure) causes respiratory swings (obliteration during inspiration) in right ventricular filling and pulmonary perfusion, ultimately resulting in right ventricular failure and dilation. Pulmonary edema was due to increased permeability, which was augmented by a modest (approximately 40%) increase in hydrostatic pressure. The lung injury and acute cor pulmonale is likely due to pulmonary microvascular in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 46 publications
1
42
2
2
Order By: Relevance
“…around 13 mmHg, and patients had signi cant PPV. ARDS has been clearly reported as a risk factor for RV failure (13,26), while in the present cohort we did not nd a higher incidence of ARDS in these patients. However, we found a certain degree of pulmonary hypertension that could be related to an increase in BMI with a history of chronic respiratory failure.…”
Section: Rv and Sepsiscontrasting
confidence: 77%
“…around 13 mmHg, and patients had signi cant PPV. ARDS has been clearly reported as a risk factor for RV failure (13,26), while in the present cohort we did not nd a higher incidence of ARDS in these patients. However, we found a certain degree of pulmonary hypertension that could be related to an increase in BMI with a history of chronic respiratory failure.…”
Section: Rv and Sepsiscontrasting
confidence: 77%
“…MV is associated with risks of ventilator-associated pneumonia, ventilator-induced lung injury, and hemodynamic instability [5][6][7][8]. Furthermore, recent reports have indicated that waiting for lung transplantation with MV support is a risk factor for increased mortality compared without MV [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…36 Recent data suggest that not only is the RV dysfunction the consequence of VILI, but also it could promote in part such a ventilator-induced lung injury (VILI). 37,38 The protective effect of prone positioning against VILI potentially could be explained by ventilatory homogeneity, a decrease in tidal hyperinflation, and homogenous distribution of strain. [33][34][35][36][37] In conclusion, a substantial body of evidence supports the pivotal role of prone positioning in reducing mortality outcomes in severe ARDS.…”
Section: Protection Against Ventilator-induced Lung Injurymentioning
confidence: 99%
“…37,38 The protective effect of prone positioning against VILI potentially could be explained by ventilatory homogeneity, a decrease in tidal hyperinflation, and homogenous distribution of strain. [33][34][35][36][37] In conclusion, a substantial body of evidence supports the pivotal role of prone positioning in reducing mortality outcomes in severe ARDS. RV failure is a predictor of mortality in ARDS, and therefore monitoring and protecting the RV should be made an integral part of a heart and lung protective strategy in severe ARDS.…”
Section: Protection Against Ventilator-induced Lung Injurymentioning
confidence: 99%